Analysis of the Effectiveness of Subsidized Fertilizer Program Distribution in Indonesia - Fatika, Yeka Hendra; Umar, Haryono; Nirmalawati, Dyah (Jurnal Doktor Manajemen (JDM), 2025)
Fertilizer subsidies represent a strategic policy instrument in Indonesia’s agricultural development agenda. Despite their significance, the implementation of subsidized fertilizer programs continues to face numerous challenges, including inaccurate targeting, weak distribution accountability, and data inconsistencies. This study aims to evaluate the effectiveness of the subsidized fertilizer program based on the "7 Right Principles" (Right Target, Type, Quantity, Price, Time, Place, and Quality). Employing a descriptive qualitative approach with mixed methods, data were collected through surveys and in-depth interviews conducted across seven provinces representing diverse geographic and socio-economic contexts. Quantitative scoring using a Likert scale yielded an average effectiveness score of 3.65 out of 5, below the 75% threshold set for effective program implementation. The findings indicate that the program has not yet achieved optimal performance. Major issues persist in the areas of beneficiary validation, timely delivery, and price transparency. The findings of this study are important for informing future policy reformulations, emphasizing several key recommendations, including the establishment of stronger verification systems, the implementation of community-based monitoring, and the enhancement of policy literacy among farmers, in order to sustainably improve the effectiveness of fertilizer subsidies.